Border Price and Export Demand Shocks for Developing Countries from Rest-of-World Trade Liberalization Using the Linkage Model - van der Mensbrugghe, Dominique; Valenzuela, Ernesto; Anderson, Kym (World Bank, Washington, DC, 2017)
The volume on agricultural price distortions, inequality and poverty begins with a global study that uses the World Bank's linkage model to examine the economic impacts in various countries, regions and the world as a whole of agricultural and trade policies as of 2004. It does so by shocking that model with the removal of all agricultural price-distorting domestic and border policies with, and without, the removal of trade policies affecting all other goods. That pair of shocks is also employed in another global study in that volume to examine the inequality and poverty implications of those price-distorting policies for more than 100 countries. Then for ten national studies reported in that volume, the Linkage model again is used, but only to provide an exogenous set of shocks to the national economy wide model employed by the authors of each developing country case study. The effects of that shock on a national economy are then compared with the effects of own-country liberalization using the same national model and the same agricultural protection rates for that country as in the global Linkage model. In this appendix the authors describe the main assumptions adopted to generate the border price and export demand shocks from agricultural and trade policy reforms by the rest of the world, and how that is communicated to the national models.